2016
DOI: 10.1136/archdischild-2016-311126
|View full text |Cite
|
Sign up to set email alerts
|

Enterostomy-related complications and growth following reversal in infants

Abstract: Around 40% of infants with an enterostomy will have an enterostomy-related complication. Whatever their weight, gestation or underlying pathology, most infants thrive after enterostomy closure and this should be considered when planning the optimal timing for this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 14 publications
2
51
2
Order By: Relevance
“…The number of complications present in one infant is rarely reported[6]. If mentioned, the rates varied between 1 and a maximum of 4 complications per patient[12,13]. In our study, the most common complication after formation was skin excoriation, which occurred in almost half of all the neonates.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The number of complications present in one infant is rarely reported[6]. If mentioned, the rates varied between 1 and a maximum of 4 complications per patient[12,13]. In our study, the most common complication after formation was skin excoriation, which occurred in almost half of all the neonates.…”
Section: Discussionmentioning
confidence: 60%
“…In most cases, more than one complication occurred, and sometimes, even three, four or five complications were observed in one patient. Previous studies also found enterostomy complications after formation to be fairly frequent, with reported rates varying between 34% and 66%[4,12,13,15-17]. The number of complications present in one infant is rarely reported[6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bethell G et al . divided patients according to complications or no complications 14 and reported that 24 patients with complications weighed less than 34 patients without complications (3655 g vs 5185 g, respectively). Older for GA and older corrected age at EF was seen in the no complications group (35 weeks vs 28.5 weeks, p = 0.01; and 36.3 weeks vs 32.6 weeks, p = 0.011).…”
Section: Discussionmentioning
confidence: 99%